2010
DOI: 10.1002/med.20209
|View full text |Cite
|
Sign up to set email alerts
|

ErbB family receptor inhibitors as therapeutic agents in breast cancer: Current status and future clinical perspective

Abstract: Breast cancer is the most common cancer diagnosed in women and the second most common cause of female cancer-related deaths, with more than one million new cases diagnosed per year throughout the world. With the recent advances in the knowledge of cellular processes and signaling pathways involved in the pathogenesis of breast cancer, the current focus of researchers and clinicians is to develop novel treatment strategies that can be included in the armamentarium against breast cancer. With the failure of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 272 publications
(340 reference statements)
0
67
0
Order By: Relevance
“…HER2, a member of the receptor tyrosine kinase family, plays a crucial role in the growth of both normal tissue and malignant tumours (Saxena and Dwivedi, 2012). HER2 overexpression is observed in 18.9-22.4% of epithelial ovarian carcinomas (Steffensen et al, 2007), and it is reported to be seen more frequently in mucinous ovarian cancers (Yan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…HER2, a member of the receptor tyrosine kinase family, plays a crucial role in the growth of both normal tissue and malignant tumours (Saxena and Dwivedi, 2012). HER2 overexpression is observed in 18.9-22.4% of epithelial ovarian carcinomas (Steffensen et al, 2007), and it is reported to be seen more frequently in mucinous ovarian cancers (Yan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1 Nevertheless, molecularbased subtype classification of breast cancer using these three molecules alone is insufficient to reflect the complex biological characteristics of the disease or meet the need for personalized care. 1,[6][7][8][9] For example, about one third of hormone receptor-positive patients benefit little from endocrine therapy according to current criteria. 1,5,10 Further, some hormone receptor-positive patients with a potentially better prognosis are subjected to intensive chemotherapy but suffer from toxicity (overtreatment), while other patients at high risk of recurrence receive inadequate treatment, leading to compromised efficacy (undertreatment).…”
mentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) is a member of the ErbB receptor family and is a new therapeutic target in solid tumors. 2 To date, four members of the ErbB receptor family have been identified, including EGFR (HER1/ErbB-1), HER2 (ErbB-2/neu), HER3 (ErbB-3), and HER4 (ErbB-4). These ErbB receptors are widely expressed in several mammalian tissues and cell types, particularly those of epithelial, mesenchymal, and neuronal origin.…”
Section: Introductionmentioning
confidence: 99%
“…They participate actively in physiological functions, such as cell proliferation and differentiation, cellcell interaction, cytokine signaling and stress responses, and in oncological activities, such as cancer cell proliferation, survival, and metastasis. 2,3 Structurally, EGFR is a transmembrane protein with an extracellular epidermal growth factor-binding domain, a transmembrane region, and an intracellular domain with ligand-activated tyrosine kinase activity. EGFR has been identified as a key cell surface receptor involved in a complex signaling network, with a binding capacity to various classes of agonists, including epidermal growth factor, transforming growth factor alpha, heparin-binding epidermal growth factor-like growth factor, amphiregulin, epiregulin, epigen, betacellulin, and neuregulin 2β.…”
Section: Introductionmentioning
confidence: 99%